Aceh farmer's acceptance of agricultural technology. Issue 1 (February 2021) - Agussabti; Rahmaddiansyah; Romano; Zahara, I
Abstract: The use of technology in rice farming is urgently needed by farmers to increase productivity and increase business efficiency. The characteristics of technological innovation consisting of relative advantages, compatibility, compatibility, trialability, and observation can influence farmers' attitudes to adopt technology. Some technological innovations used by farmers using a machine combining harvesters, tractors, Ciherang-type superior seeds, and planting. The purpose of this research is to conduct a consistent constitutional trial of various technological innovation variables and public acceptance of the technology being introduced. This research was conducted in Aceh Besar and Pidie Jaya districts using the Confirmatory Factor Analysis (CFA) analysis model and descriptive analysis. The final results of this study are expected so that the government can adopt policies that are appropriate to the needs of technology in agriculture that can be accepted by the community.